2016
DOI: 10.1002/ejoc.201600220
|View full text |Cite
|
Sign up to set email alerts
|

Cascade C–C and C–N Bond Formation: A Straightforward Synthesis of Phenanthridines and Fused Quinol­ines

Abstract: A Pd‐catalyzed cascade process has been developed for the synthesis of quinoline and phenanthridine derivatives from various β‐chloro α,β‐unsaturated aldehydes and 2‐chloroaryl aldehydes, respectively, in good to high yields. The reaction proceeds through Pd‐catalyzed cascade carbon–carbon and carbon–nitrogen bond formation in a single reaction vessel. The requisite β‐chloro α,β‐unsaturated aldehydes were efficiently synthesized from their corresponding carbonyl compounds. The use of the ligand Sphos with Pd(O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…At first, benzimidazole 24 coordinate with Pd II to form 27, which was followed by an ortho CÀ H activation to generate a five-membered palladacycle 28. Gogoi et al explored [20] a cascade Suzuki crosscoupling/condensation reaction towards the preparation of fused quinoline and phenanthridine derivatives by the reaction of β-chloro α, β-unsaturated aldehydes, derived from corresponding ketones via Vilsmeier-Haack-Arnold chloro formylation reaction, and 2chloroaryl aldehydes 33 in presence of (2-aminoaryl) boronic acid pinacol esters 34 in 2016. This one-pot reaction goes through Pd-mediated CÀ C and CÀ N bond formation.…”
Section: Palladium-catalyzed Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…At first, benzimidazole 24 coordinate with Pd II to form 27, which was followed by an ortho CÀ H activation to generate a five-membered palladacycle 28. Gogoi et al explored [20] a cascade Suzuki crosscoupling/condensation reaction towards the preparation of fused quinoline and phenanthridine derivatives by the reaction of β-chloro α, β-unsaturated aldehydes, derived from corresponding ketones via Vilsmeier-Haack-Arnold chloro formylation reaction, and 2chloroaryl aldehydes 33 in presence of (2-aminoaryl) boronic acid pinacol esters 34 in 2016. This one-pot reaction goes through Pd-mediated CÀ C and CÀ N bond formation.…”
Section: Palladium-catalyzed Reactionsmentioning
confidence: 99%
“…Zhu et al demonstrated [29] a palladium-mediated double isocyanide insertion reaction to construct distinct heterocyclic scaffolds 80, containing both phenanthridine and carbazole moiety from readily available substituted 2-iodo-2'-isocyano-1,1'-biphenyls 79 through copper-catalyzed Ullmann CÀ N bond forming reaction. After vigorous optimization studies, they found that using 2 mol% Pd(OAc) 2, 20 The copper-mediated intramolecular Ullmann reaction gives the desired product 80.…”
Section: Palladium-catalyzed Reactionsmentioning
confidence: 99%
“…Recently, Borah and Gogoi reported a Pd‐catalyzed synthesis of phenanthridine 140 through cascade carbon–carbon and carbon–nitrogen bond‐formation reactions by using 2‐chloroaryl aldehyde and 2‐aminophenylboronic acid pinacol ester as the starting substrate with the aid of Pd(OAc) 2 /Sphos system (Sphos=2‐dicyclohexylphosphino‐2′,6′‐dimethoxybiphenyl; Scheme ) …”
Section: Benzaldo‐x Bifunctional Building Blocks and Their Heterocyclmentioning
confidence: 99%
“…This scaffold has continuously fascinated the synthetic and medicinal chemists owing to its broad application in medicinal chemistry [3–7] . Functionalized indoles are known to exhibit remarkable binding ability as ligand for different type of receptors, which make them one of the most “privileged scaffolds”, firstly proposed by Evans and co‐workers in medicinal chemistry [8–10] . Indole nucleus is present in an enormous range of natural products varying from simple small molecules like serotonin to complex alkaloids, which are significant for human and animal health (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Functionalized indoles are known to exhibit remarkable binding ability as ligand for different type of receptors, which make them one of the most "privileged scaffolds", firstly proposed by Evans and co-workers in medicinal chemistry. [8][9][10] Indole nucleus is present in an enormous range of natural products varying from simple small molecules like serotonin to complex alkaloids, which are significant for human and animal health (Figure 1). [11] In addition, this scaffold is used in cosmetics, reprography, information storage, plastics, solvents, antioxidants, and vulcanization accelerators.…”
Section: Introductionmentioning
confidence: 99%